MEASLES IN VACCINATED CHILDREN 1.5 TO 3 YEARS OF AGE IN RURAL COMMUNITY OF DISTRICT PESHAWAR, PAKISTAN - Khan, Aftab; Ullah, Obaid; Ambreen, Mrs; Ahmad, Israr; Din, Meraj ud (Journal of Ayub Medical College Abbottabad, 2015)
Background: In many developing countries measles is a leading cause of childhood morbidity and mortality. Despite of vaccination thousands of children have been infected by measles virus during last couple of years in Pakistan. The objective of this study was to determine the measles vaccination coverage rate and frequency of measles among vaccinated children of age 1.5-3 years in rural community of district Peshawar. Methods: The cross-sectional study was carried out among 385 children aged 1.5-3 year of rural community of Peshawar. After taking informed consent from parents/guardians a predesigned questionnaire was filled. Evidence of vaccination and measles history was taken by vaccination card, doctor prescription and parent/guardian recall. Data was gathered and analysed by using SPSS-16. Results: Of the 385 children, 361 (93.7%) were vaccinated against measles at 9 month. It was found that 27 (7.48%) vaccinated children had measles history of which 23 (6.74%) were infected after 9 month vaccination. One hundred and ninety-two (49.8%) children were vaccinated both at 9 and 15 months, and 14 (7.29%) dual vaccinated children had a measles history, 9 among them (4.68%) were infected after taking both measles doses. Conclusion: The occurrence of measles among vaccinated children and low coverage rate of second dose of measles vaccine raises many questions about vaccination program and its efficacy. Further studies are needed to evaluate the influence of other predisposing factors like vaccine quality, manufacturer, supply, cold chain, handling, nutritional status of children and technical approach, on measles vaccine efficacy.